Hubungan Penguasaan Kosakata dan Penguasaan Kalimat dengan Kemampuan Menulis Deskripsi - Mahpudoh, Mahpudoh (Universitas Mathla'ul Anwar Banten, 2019)
This study aims to determine the relationshop of mastery of vocabulary and mastery of sentences with the ability to write descriptions. The research is limited to the problem of the ability to write descriptions as a dependent variable, while mastery of vocabulary and mastery of sentences as independent variables. The limitation of this problem is limited to the assumption that these two factors have a relationship with the ability to write descriptions. The method used in this study is a survey method with correlational regression techniques. Population and sample in this study were students of class XII MA Attoyyibiyah Serang Banten in the academic year 2013-2014. Affordable population is 160 students, wich is also a sample framework. To determine the sample spread there is no absolute provision. However, in determining the sample it is necessary to consaider the homogeneity or heterogeneity of the population and the population size so that the sample is set at 35 students. The results of this study can be concluded: (1) there is a positive relationship with vocabulary mastery with the ability to writing descriptions. (2) there is positive relationship to mastery of sentences with the ability to write descriptions and (3) there is a positive relationship of mastery of vocabulary and mastery of sentences with the ability to write descriptions.